Analisis Kebutuhan Pengembangan E-modul Statistika Berbasis Kontekstual Untuk Siswa Kelas VIII - Nuriah Nuriah; Syamsuri Syamsuri; Yuyu Yuhana; Hepsi Nindiasari (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to analyze the needs of students and teachers in the development of contextual-based statistical material e-module materials for grade VIII students. This research uses qualitative descriptive method for initial analysis of product development by making junior high school or MTS math teacher in Pandeglang and MTs student Malnu Kadukaung as research subjects. Collection of data instruments using questionnaires via Google Forms. The study involved 15 teachers and 21 students. From this study btained the results that students still have difficulty solving problems or contextual problems even though at the time of learning the teacher has associated statistics with the concept of daily life, and also special teaching materials such as e-modules are not yet available so that students need alternative teaching materials in order to learn statistics to be easy and interesting. Whereas according to the teacher, teaching materials in the form of contextual-based e-modules need to be developed because teachers have not used e-modules as statistically specific teaching materials. So far, the teaching materials used by teachers have not been integrated with contextual approaches, as well as the teacher's positive response to the development of teaching materials in the form of contextual-based e-modules.